Effect of COVID 19 Pandemic on Stroke Care and Admission - Single Centre Study - Mosab, Alguthmi; Mahmoud, Alshanqiti; Mohammed, Almansour; Mohammed, Saeed Alqahtani; Muhannad, Asiri; Saeed, Alzahrani (Journal of Neurological Research And Therapy, 2021)
Background By the start of year 2020, the whole world was attacked by a rapidly spreading epidemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) which later was classified by WHO as Pandemic. some physicians reported multiple neurological manifestations including cerebrovascular strokes in patients with severe infection. Aim to assess the incidence of admitted stroke cases during 2019 in comparison to 2020 during COVID-19 pandemic in King Fahd Hospital, Saudi Arabia. Methodology A record based retrospective comparative study was conducted by reviewing all medical records for patients who admitted with stroke at King Fahd Hospital during March and April 2019 and March and April 2020. All data were extracted from patients’ medical files included personal data, nationality, date of admission, and stroke related data. Results The study included 121 patients whose ages ranged from 33 to 98 years with mean age of 59.9 years. At March 2019, there were 45 cases compared to 26 in March 2020. In April 2019 there were 20 admitted stroke cases compared to 30 in April 2020. Regarding clinical features of admitted stroke cases, Table 3 illustrates that 36.9% of stroke cases in 2019 were small vessel stroke compared to 58.9% of 2020 cases. Conclusions & Recommendations In conclusion, the study revealed there was no recorded significant change in the trend of admitted cases with stroke before and during COVID-19 pandemic.
Keywords: breath-hold protocol; fMRI technique; Cerebral Decompression illness